PTEN: A Thrifty Gene That Causes Disease in Times of Plenty? - Venniyoor, Ajit (Frontiers in Nutrition, 2020)
The modern obesity epidemic with associated disorders of metabolism and cancer has been attributed to the presence of “thrifty genes”. In the distant past, these genes helped the organism to improve energy efficiency and store excess energy safely as fat to survive periods of famine, but in the present day obesogenic environment, have turned detrimental. I propose PTEN as the likely gene as it has functions that span metabolism, cancer and reproduction, all of which are deranged in obesity and insulin resistance. The activity of PTEN can be calibrated in utero by availability of nutrients via the methylation arm of the epigenetic pathway. Deficiency of protein and choline has been shown to upregulate DNA methyltransferases (DNMT), especially 1 and 3a; these can then methylate promoter region of PTEN and suppress its expression. Thus, the gene is tuned like a metabolic rheostat proportional to the availability of specific nutrients, and the resultant “dose” of the protein, which sits astride and negatively regulates the insulin-PI3K/AKT/mTOR pathway, decides energy usage and proliferation. This “fixes” the metabolic capacity of the organism periconceptionally to a specific postnatal level of nutrition, but when faced with a discordant environment, leads to obesity related diseases.